A study of vitiligo in type 2 diabetic patients - Leena Raveendra; Rekha N Hemavathi; Sushma Rajgopal (Wolters Kluwer Medknow Publications, 2017)
Context: Diabetes mellitus is associated with many skin manifestations including vitiligo. Vitiligo occurs more commonly in Type 1 diabetes mellitus. A few recent studies have shown its increased occurrence in Type 2 diabetes mellitus. Aims: This study aims to study the prevalence of vitiligo in Type 2 diabetic patients and to compare the prevalence of vitiligo in age- and sex-matched group of nondiabetic population. Settings and Design: The present study was a hospital-based cross-sectional study conducted in the Department of Dermatology in a tertiary care hospital. Subjects and Methods: Six hundred consecutive consenting patients of Type 2 diabetes were included in the study group and age- and sex-matched controls were healthy nondiabetic adult volunteers attending the Department of Dermatology. Fasting and postprandial blood sugar levels were done. A complete history, physical examination, and wood's lamp examination to detect vitiligo were conducted. In all those with vitiligo, the type of vitiligo was noted. Statistical Analysis Used: Data were analyzed using SPSS software version 20.0. Comparison between the presence of vitiligo in cases and controls was done using Chi-square test with P = 0.05 for significance. Results: Vitiligo was seen in 12% of cases and 6% of control group which was statistically significant (P < 0.01). There was no significant difference between cases and controls with respect to type of vitiligo. Conclusions: Vitiligo can occur in Type 2 diabetics as seen in our study and few other recent studies. The exact pathogenesis is not very clear and needs further consideration.